PUBLIC SPEAKING AND COPYWRITING IN SME’S PRODUCT DEVELOPMENT AT PLUT-KUMKM BATU CITY, EAST JAVA PROVINCE - Ferdian, Putu Aditya; Mardiyanta, Antun; Irianto, Jusuf; Suaedi, Falih; Supeno, Eko; Asmorowati, Sulikah; Setijaningrum, Erna; Supramudyo, Gitadi Tegas; Wardiyanto, Bintoro; Triana, Rochyati Wahyuni; Haryono, Nanang; Keban, Philipus; Soegiono, Agie Nugroho; Hariani, Nurul Jamila; Bahar, Adam Amin (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This community service aims to increase sales and product promotion through efforts to improve public speaking and copywriting skills for business actors. The target of this community service activity is business actors who are members and are fostered by the Integrated Business Service Center for Cooperatives and UMKM (PLUT-KUMKM) in Batu City, East Java. For this reason, the Department of Public Administration of Airlangga University will partner with the Integrated Business Service Center for Cooperatives and UMKM (PLUT KUMKM) in Batu City, East Java to hold a community service program at the location. Community service activities will provide public speaking and copywriting training for business actors who are members of the PLUT-KUMKM in Batu City. Activities will be carried out through three main stages: preparation, implementation, and evaluation. The preparation stage involves collecting and compiling relevant political and civil literacy materials. Furthermore, the implementation stage will involve counseling, workshops, and group discussions to provide in-depth understanding to business actors. The evaluation stage will be carried out to measure the effectiveness of the program and obtain feedback from participants. This activity is expected to provide a fundamental contribution to increasing sales, promotions, marketing coverage areas and the quality of MSME products. Through this community service activity, it is hoped that business actors in the PLUT KUMKM Batu City will become more aware of how public speaking and copy writing in a business product will compete in a dynamic environment by utilizing digital technology.